1996
DOI: 10.1097/00007632-199601150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Fusion for Lumbar Spinal Stenosis in Elderly Patients and Its Significance

Abstract: The definition of instability by Posner's method proved useful for selecting elderly patients with instability for fusion treatment. Fusion with instrumentation should be performed on elderly patients with instability after decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 12 publications
2
70
1
4
Order By: Relevance
“…Further, and in contrast to the present study, none of the observational studies declared using a consecutive series of all eligible patients. Three papers from Japan used JAO scores [15,21,27] and one used ODI and SF 36 [5]. To pool the data, an attempt was made to dichotomise each clinical outcome into ''satisfactory'' or ''not satisfactory'', since the various outcome instruments were not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Further, and in contrast to the present study, none of the observational studies declared using a consecutive series of all eligible patients. Three papers from Japan used JAO scores [15,21,27] and one used ODI and SF 36 [5]. To pool the data, an attempt was made to dichotomise each clinical outcome into ''satisfactory'' or ''not satisfactory'', since the various outcome instruments were not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many papers with class II and III evidence levels advocating concomitant spinal fusion and arthrodesis to improve outcomes and avoid late instabilities, even in patients without spondylolisthesis or spinal deformities [29][30][31][32][33][34] . It is known that when more than 30% of the articular facets are removed bilaterally, we have a greater probability of developing late instability, justifying fusion in patients subjected to large decompressive surgeries 35 .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The main objective of this review was to analyze the benefit of concomitant fusion in decompressive surgery for DS (Martin et al 2007). Based on two RCT's (Herkowitz and Kurz 1991;Bridwell et al 1993) and 5 observational studies (Feffer et al 1985;Lombardi et al 1985;Satomi et al 1992;Yone et al 1996;Ghogawala et al 2004) it was concluded that a concomitant fusion in DS surgery conferred a better outcome than decompression without fusion. The two cited RCT's (Herkowitz and Kurz 1991;Bridwell et al 1993) were however noticeably flawed in their design in terms of randomization (pseudo-randomized or not described adequately), blinding (not described) and the lack of validated general or specific patient related outcome measures as end point variables (Martin et al 2007).…”
Section: Spinal Fusion and Outcomementioning
confidence: 99%
“…The few retrospective studies that have analyzed outcome of decompression compared to decompression and fusion in patients with DS include few patients, seldom with consecutive inclusion, patients with and without additional scoliosis, and rarely use validated outcome measures (Feffer et al 1985;Lombardi et al 1985;Satomi et al 1992;Yone et al 1996). In spite of a low level of evidence, it is worth noting that these studies usually favor fusion in DS.…”
Section: The Role Of Spinal Fusion In Dsmentioning
confidence: 99%